Autonomous and direct control of robotic arms for surgical applications - Tan, Rui Bin (Nanyang Technological University, 2024)
This paper delves into the integration and comparative evaluation of autonomous robotic systems and foot teleoperation within diverse surgical tasks. By employing deep learning models in computer vision and natural language processing, the autonomous system can augment the capabilities and control of robotic arms in surgical procedures. Throughout the paper, a meticulous examination and demonstration of the workflow showcases the robot involvement in procedures encompassing puncturing in simple sutures and microsurgical anastomosis which includes suture transfer, tissue cutting, and suture manipulation. These meticulously designed procedures underscore precision and efficiency, effectively demonstrating the potential of robotics in surgical applications. By conducting a comprehensive pilot test, the study elucidates the trade- offs between accuracy, effort, and workflow efficiency inherent in autonomous systems and foot teleoperation. This analysis intricately explores the nuances of control interfaces, examining the performance, user experiences, and preferences of each system. Detailed insights into user experiences, system performance, and trajectory efficiency are provided, offering a comprehensive understanding of the strengths and limitations of each control interface.